The Long Journey of Gracia Mendes - Marianna D. Birnbaum (Central European University Press, 2003)
The historical biography of a true Jewish heroine in her day, Gracia Mendes. Born in 1510 in Portugal, the book details this woman's extraordinary personality until her death in 1569 in Constantinople (today's Istanbul). Her life exemplified a perseverance by the Jewish culture to survive and triumph even in the worst of conditions. As a young girl, Gracia secretly married successful Jewish spice trader, Francisco Mendes. But at age 27 she became a widow, yet she went on to raise her children...